Learner Agency, Motive, and Self-Regulated Learning in an Online ESL Writing Class - Zhang, Jie (IALLT Journal of Language Learning Technologies, 2013)
Online learning has become a viable popular alternative to traditionalESL writing classes over the past decade. However, the effectivenessand validity of online ESL learning remains controversial.Furthermore, most researchers have used surveys to assess studentperceptions of online learning. This study presents a case study of twoparticipants in an online ESL writing course at a university in theNortheastern United States. Using activity theory as a framework, Iexplore what makes a successful learner in an online environment andhow learner agency, motive, and self-regulation impact studentperformance and academic achievement in the online learning context.Data from different sources were collected to provide a triangulatedanalysis. Results suggest that learners who employ good self-regulationstrategies and are motivated to learn and adapt tend to benefit morefrom the online learning experience, while students who do not employsuch strategies and are motivated solely to fulfill a degree requirementare more likely to be frustrated. The results also reveal that thephysical distance created by technology could be a challenge for thosewho do not seek assistance from instructors or peers. In other words,learners need guidance and support on how to be self-motivated andself-directed in the online environment. I also discuss how to effectivelydesign and deliver an online ESL course.